Accumulation of Knowledge by Strategic Public Procurement through Public-Private Partnerships for Service Innovation in Japan - Taeko Suehiro; Kumiko Miyazaki (STI Policy and Management Journal, 2019)
This study focuses on how governments strategically procure public service through Public–Private Partnership (PPP) – or more specifically, Private Finance Initiative (PFI) arrangements. PPP/PFI is recognised as a key element of demand-oriented innovation policy in the field of social infrastructure.  However, owing to the considerable uncertainty of each project, the benefits of PPP/PFI are subject to debate, as is the role of public procurement in fostering public service innovation. The purpose of this study is to examine how governments strategically procure public services from construction firms in Japan. We conduct a comparative case study of two waste-to-energy PFI projects to clarify how governments improved the public procurement.The results suggest the following: first, municipalities utilise a greater extent of other municipalities’ experience through external experts (i.e. Ministry of Environment, advisors, committee members and potential bidders) and standardised service criteria. Second, the codification of tacit knowledge, which both public and private entities have gained from previous projects, is important for securing a robust and routinised service level and reaping the benefits of the scale of repetition. Third, interaction with private companies in the bidding process with an appropriate manner would foster public service innovation. Governments' capability development through the use of internal and external resources can create space for private companies to provide better service by accumulating tacit knowledge within the projects. Keywords: Public procurement; Public–Private Partnership; Private Finance Initiative; Service innovation; Construction firm; Waste-to-energy